(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2016)
The present article focuses the status of plant diversity of Dhaka University campus. A total of 541 plant species have been recorded from the campus area. These species are assigned to 117 families. For each species local name, scientific name, family and habit have been provided. Species presentation in the families varied from 1 to 26. 47% species belongs to 16 families and 53% species belongs to others 101 families. Euporbiaceae is the largest family in the Dicotyledon having 26 species whereas Liliaceae is the largest family in Monocotyledon having 18 species. Among the recorded species, 37% are represented by herbs, 29% by trees, 21% by shrubs, 11% by climbers, 2% by epiphytes and 0.2% by parasites. Plant species recorded in the campus categorized into different purpose groups. The result showed that 59% plant species represented by native species whereas 41% plant species represented by exotics. The survey spotted the presence a number of threatened species of Bangladesh in the gardent of the campus. Such species are Corypha taliera, Podocarpus nerifolia, Mangifera sylvatica, Willoughbia edulis, Hydnocarpus kurzii, Gloriosa superva, Entada redii, Hedychium coccinium and Vandopsis gigantea. J. Asiat. Soc. Bangladesh, Sci. 42(1): 49-68, June 2016